Mister Sandman, Bring Me Good Marks! On the Relationship Between Sleep Quality and Academic Achievement - Stijn Baert; Eddy Omey; Dieter Verhaest; Aurélie Vermeir (Institute for the Study of Labor (IZA), 2014)
This study assesses the relationship between sleep quality and academic achievement. We survey college students about their sleep quality by means of the Pittsburgh Sleep Quality Index (PSQI) before the start of their first exam period at university. PSQI scores are matched with course marks in this first exam period. Instrumenting PSQI scores by sleep quality during secondary education, we find that increasing total sleep quality with one standard deviation leads to 4.85 percentage point higher course marks.
Keywords: I10; J24; I23; 330; economics of education; economics of health; economics of sleep; academic achievement; sleep quality